UMPSA celebrates 94 Doctor of Philosophy graduates in meaningful Hooding Ceremony - Nur Hartini, Mohd Hatta (UMPSA, 2025)
KUANTAN, 7 November 2025 – A total of 94 Doctor of Philosophy (PhD) graduates were celebrated in conjunction with the Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) Hooding Ceremony for PhD Graduands 2025 held at Swiss-Belhotel, Kuantan.